Factors Affecting Incidence of Uterine Torsion in Egyptian Buffaloes (Bubalus bubalis) and its Response for Rolling - Zaher, H.A.; Swelum, A.A.; Amin, S.; Eidaroos, A.; Hazzaa, A.M.; Sharifi, S. Al (Journal of Buffalo Science, 2017)
Objective: The present work was planned to study the incidence of uterine torsion in Egyptian buffaloes as well as its prognosis after mechanical treatment. Methods: A total number of 35 buffaloes of different ages, parities and stage of pregnancy with complain of colic and anorexia were included in the present study. These animals were examined rectally to detect stage of pregnancy, degree, direction, duration, location of uterine torsion. Mechanical handling of torsion cases and prognosis of recovered cases was performed. After birth, sex of new born was also recorded. Results: The torsion of uterus mostly occurred in pleuriparous buffaloes (100%) in right side (85.7%) during second half of pregnancy (100%). Most cases were postcervical (85.7%) during the early stage (7 and 8 months). Torsion also may occur during labour (17.4%) where the cervix was dilated after correction. Most cases of uterine torsion occur in stabled animals for long period (97%). The uterine torsion associated with male calves (65.7%) as well as with large size calves (40-50kg) and majority of the calves were in normal position. The first foetal sac expelled in majority of cases was amniotic sac (97%) with few cases of placental retention. Uterine torsion with short duration (1-6 h) usually needs 1-2 rolls only for correction and usually takes 0-6h (100%) for cervical dilatation. Occurrence of uterine torsion for above three days usually did not respond for rolling. Conclusion: Uterine torsion usually occurs in old stabled animal with good BCS during green season at last month of pregnancy. The right sever and post cervical torsion were the most common type of torsion. Rapid diagnosis of uterine torsion within 6 h usually results in good prognosis even in severe cases.